Identification of an Intercistronic Internal Ribosome Entry Site in a Marek's Disease Virus Immediate-Early Gene - Tahiri-Alaoui, Abdessamad (American Society for Microbiology (ASM), 2009)
In this study, we have identified an internal ribosome entry site (IRES) from the highly infectious herpesvirus Marek's disease virus (MDV). The IRES was mapped to the intercistronic region (ICR) of a bicistronic mRNA that we cloned from the MDV-transformed CD4(+) T-cell line MSB-1. The transcript is a member of a family of mRNAs expressed as immediate-early genes with two open reading frames (ORF). The first ORF encodes a 14-kDa polypeptide with two N-terminal splice variants, whereas the second ORF is contained entirely within a single exon and encodes a 12-kDa protein also known as RLORF9. We have shown that the ICR that separates the two ORFs functions as an IRES that controls the translation of RLORF9 when cap-dependent translation is inhibited. Deletion analysis revealed that there are two potential IRES elements within the ICR. Reverse genetic experiments with the oncogenic strain of MDV type 1 indicated that deletion of IRES-controlled RLORF9 does not significantly affect viral replication or MDV-induced mortality.